ANALISIS PROFITABILITAS BANK UMUM SYARIAH YANG MENGGUNAKAN RASIO RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) - Muhammad Ash-Shiddiqy (IAIN Batusangkar, 2019)
The purpose of this study is to understand the difference between Islamic banks' profits beforeand after interest restrictions on conventional bank deposits based on Supervision Acts No. SP-28 DKNS /OJK / 9/2014. The policies of Financial Services Authority can be measured into two profitability ratios:(1) return on assets (ROA), and (2) return on equity (ROE). There were 11 SHARIA banks in Indonesiaselected through purposive sampling technique. Secondary data were the quarterly report of the SHARIABank (six quarters), which focuses on the three quarters before and after implementing the policy. Datawere tested using hypothesis testing through paired sample t-tests with a significant level at 5% (α =0.05). The results of this study indicate that the profitability of SHARIA Banks projected by ROA and ROEhas differences before and after the conventional bank deposit interest rate.